Serum biomarkers in extramammary Paget disease. (1st September 2019) - Ellis, R.
Abstract: Linked Articles : Mijiddorj et al . Br J Dermatol 2019; 181 :505–511 . Nakamura et al . Br J Dermatol 2019; 181 :535–543 .